Characterization of a novel streptococcal heme-binding protein SntA and its interaction with host antioxidant protein AOP2. (October 2017) - Wan, Yun; Zhang, Sihua; Li, Lu; Chen, Huanchun; Zhou, Rui
Abstract: Efficient iron acquisition is critical for bacteria's survival, virulence and pathology of diseases. The largest reservoir of iron in mammals is incorporated into heme, which can be acquired by bacterial pathogens as a nutritional iron source. In this study, a cell wall protein SntA of Streptococcus suis serotype 2 (SS2) was characterized as a novel heme-binding protein by using the pyridine hemochrome assay and ICP-MS measurement. Yeast two-hybrid and pull-down assays revealed that the SntA protein could interact with the host antioxidant protein AOP2 (Antioxidant protein 2). The oxidation of hemoglobin could be promoted by adding the recombinant SntA into the hemolysates. Animal experiments demonstrated that SntA was associated with in vivo survival and pathogenesis of SS2. This is the first report that a streptococcal heme-binding protein can interact with a host antioxidant protein and consequently inhibit its antioxidant activity. These findings may provide new insights into bacterial cell wall functions and pathogen-host interactions. Highlights: SntA is a novel type of heme-binding protein involved in iron uptake in pathogens. SntA could interact with the host peroxiredoxin AOP2. This interaction inhibits the antioxidant activity of AOP2. This interaction accelerates hemoglobin oxidation during the infection of SS2. SntA was associated with in vivo survival and pathogenesis of SS2.